Teachers' Strategies for Managing Disruptive Behavior in The Classroom During The Learning Process - Mila Hasanah; Yasir Arafat; Mahyudin Barni; Ahmad Thib Raya; Andika Aprilianto (Nazhruna: Jurnal Pendidikan Islam, 2024)
This study aims to examine the strategies employed by teachers at Madrasah Ibtidaiyah Negeri 2, Banjarmasin to manage disruptive behavior in the classroom during the learning process. The research employs a qualitative methodology, utilizing descriptive analysis based on data gathered from semi-structured interviews with teachers and a review of related literature. This approach allows for a comprehensive understanding of the practical techniques used by educators in real-time classroom settings and assesses their effectiveness in creating a conducive learning environment. The findings reveal that teachers at Madrasah Ibtidaiyah Negeri 2 effectively utilize a combination of behaviorist and constructivist strategies to manage and mitigate disruptive behaviors. Key strategies include the application of positive reinforcement to encourage desirable behaviors and the establishment of clear, consistent rules to provide structure. Additionally, the use of engaging and interactive teaching methods has been shown to significantly reduce instances of disruptive behavior by maintaining high levels of student involvement and interest. Despite these positive outcomes, challenges such as the diverse nature of the student body and varying degrees of parental support pose obstacles to the uniform application of these strategies. The research indicates that while the employed strategies are generally effective, they require continuous adaptation and support to address these challenges adequately.